Evaluasi Program Puspaga Dalam Upaya Pencegahan Kekerasan Anak Di DP3APPKB Surabaya : (Studi Kasus Layanan Konseling) - Rismaul Mukhaiyaroh; Arif Darmawan; Endang Indartuti (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
Violence against children still often occurs in the city of Surabaya. Families still face obstacles in solving problems due to parents' lack of understanding in caring for children. Families need a place for consultation and support as well as learning processes so that the scope of the family can be maximized. The Surabaya city government is trying to protect children. One of the efforts of the Surabaya City Government is that the Ministry of Women's Empowerment and Child Protection (PPPA) has the best Family Learning Center (PUSPAGA) program. PUSPAGA services are under the auspices of the Surabaya City Women's Empowerment and Child Protection, Population Control and Family Planning (DP3APPKB) Service. PUSPAGA Surabaya City is present in the community for those who need services related to family problems, including childcare information. The aim of this research is to find out how the PUSPAGA program is evaluated in efforts to prevent child violence in DP3APPKB Surabaya (Counseling Service Case Study). This study uses a qualitative method. The theory used belongs to the PUSPAGA Program using Ripley's 7 evaluation indicators (Purwanto & Sulistyastuti, 2012), namely access, coverage, frequency, bias, service delivery, accountability, suitability of the program to needs. The PUSPAGA program for Surabaya City Counseling services has been running well in every indicator. Even so, the Surabaya City Government should be more proactive in informing the public about the existence of PUSPAGA services in the City of Surabaya.